Empowerment and Development of Elderly Potential Facing Retirement Period - Tomy Hendrawanto (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2016)
There are many things that must be prepared for the elderly when facing retirement, so that they can live healthy, active and independent. This paper aims to explore and describe the empowerment and development of elderly potential, they should be able to determine the career options after entering retirement. The article uses a qualitative approach writing, data are analised through descriptive technique. This paper is based on the discovery of a problematic condition associated with the elderly and retired, the empowerment and development of elderly potential facing retirement. The purpose of this study was to identify the factors that cause variety of problems that arise in order to provide practical solutions. The result is that there are three things for the elderly to the empowerment and development their potential career. First, to continue his career in accordance with the career of origin, same institution and place or in different place but same plane. Second, continue his career outside the home career path with self-employed and services. Third, enjoying retirement by increasing the worship, close to the family, do their hoby and socializing. It can be concluded that the empowerment and development potential of the elderly is an effort to learn about and appreciate the process of life long career when facing retirement.